PENGARUH KEBIJAKAN KUOTA 95% TERHADAP STANDAR PENDIDIKAN DI KOTA PONTIANAK - Haris Munandar E.01108109 (PublikA, Jurnal Ilmu Administrasi Negara, 2013)
This research aims to examine and analyze the effect on the standard of education resources. The data was collected through questionnaires and conducted in 45 teachers at SMAN 3 Pontianak. Analysis of the data in this study using Pearson product moment test.To test the hypothesis of the study conducted by Pearson Product Moment correlation analysis. The analysis shows that the resource does not have a positive effect on educational standards. From the results of hypothesis testing showed that r count for 0.095 is smaller than the table r 0294. with N amounted to 45 respondents. Based on the count r 0.095 compared with a table of guidelines influence the interpretation of the strength is very low. From the calculation of the coefficient of determination obtained resource contribution to the standard of education 0.9%. Thus, there is no positive effect 95% quota Policy Toward Education Standards in Pontianak.Creatinga policyshould take into accountexisting resourcesbe itfinancial, authority, human resources, andthe potential that existsinthe currentoverallpolicythathas benefitsandpositiveimpactof educational standards. Keywords: educationalresources, standardizedprocesses, andEducationalStandards